Does Public Transit reduce Car Travel Externalities? - Martin W. Adler; Jos N. van Ommeren (Tinbergen Institute, 2015)
One of the main unanswered questions in the field of urban economics is to which extent subsidies to public transit are justified. We examine one of the main benefits of public transit, a reduction in car congestion externalities, the so-called congestion relief benefit, using quasi-natural experimental data on citywide public transit strikes for Rotterdam. On weekdays, a strike induces car speed to decrease only marginally on the highway ring road (by 3 percent) but substantially on inner city roads (by 10 percent). During rush hour, the strike effect is much more pronounced. The congestion relief benefit is substantial, equivalent to about half of the public transit subsidy. We demonstrate that during weekends, car speed does not change noticeable due to strikes. Further, we show that public transit strikes induce similar increases in number of cyclists as number of car travelers suggesting that bicycling-promoting policies to reduce car congestion externalities might be attractive.
Keywords: H76; J52; L92; R41; 330; transit subsidies; public transit; traffic congestion; congestion relief benefit; strike